Analysis Of Cost Of Production PT. Longgeng Prosperous Industry - Fausta Ari Barata; Ulfi Pristiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Examining the production costs employed by PT. Lasting Prosperous Industry is the aim of this study. The research approach used in this study was qualitative research methodology. The population and sample of the study were selected to represent the societal issues that the PT firm deals with. Langgeng Makmur Industri uses field research, including observation, interviews, and documentation, as well as library research. The results of the investigation show that PT. Langgeng Makmur Industri's production cost approach does not fully utilize current theory; yet, because the company levies a 3% reserve fee, the estimation procedure is nevertheless regarded as normal.